POSTMODERN INTERCULTURAL COMMUNICATION: BEYOND NATIONAL AND ETHNIC IDENTITIES - Chastagner, Claude (Armenian Folia Anglistika, 2022)
New modes of communication gradually emerged at the end of the 20th century, shifting the focus of attention from national and ethnic criteria to the more complex and multifarious ones suggested by the intercultural paradigm. This shift parallels the global tendency to move away from univocal, modernist perspectives to the more complex, and ambiguous postmodern ones. Downplaying the role of fixed national or ethnic identities in the communication process, and refusing simplifications and generalizations to emphasize instead fluidity and complexity, this new paradigm has had consequences on the lives of sub-groups and minorities, and on the communication process as a whole.